1970
DOI: 10.1159/000458349
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Activities in Human Liver

Abstract: Biologie, technical, and methodic problems in the determination of enzyme activities in human hepatic tissue are evaluated critically and enzyme activities of normal liver, as well as their alterations in diseases of the liver and in inborn errors of metabolism are described on the basis of personal findings and a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
21
2

Year Published

1975
1975
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 76 publications
4
21
2
Order By: Relevance
“…4). G6PD activity increases and ICD activity decreases characteristically in the injured livers according to previous studies (5,9,11,13). The results of present study agree with these previous studies.…”
Section: Subjectssupporting
confidence: 93%
See 2 more Smart Citations
“…4). G6PD activity increases and ICD activity decreases characteristically in the injured livers according to previous studies (5,9,11,13). The results of present study agree with these previous studies.…”
Section: Subjectssupporting
confidence: 93%
“…NADPH is required for many synthetic processes, such as those of fatty acid and steroids. In various types of liver injury, the G6PD activity increases (4,9,11,13), although the activity of most enzymes of the glycolytic and tricarboxylic acid (TCA) cycles decreases. Isocitrate dehydrogenase (ICD) is one of the important dehydrogenase enzymes which produces NADPH in the TCA cycle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have shown the increased G6PD activity and decreased ICD activity in various kinds of liver injuries in assays of liver homogenates (11,14). The present experiment showed the increased G6PD activity and decreased ICD activity by the ultramicrochemical method in the central area which was the most severely damaged area in the CC14-injured liver.…”
Section: Discussionsupporting
confidence: 61%
“…NADPH is required for many synthetic processes, such as fatty acid and steroid synthesis. In various kinds of liver injury, the activity of G6PD increases (11,14), although the activity of most enzymes of the glycolytic and tricarboxylic acid cycles decrease. Isocitric acid dehydrogenase (ICD) is one of the important dehydrogenase enzymes which produces NADPH in the TCA cycle.…”
mentioning
confidence: 99%